ARHGEF10L Promotes Cervical Tumorigenesis via RhoA-Mediated Signaling. (24th March 2021) - Tang, Junyi; Fang, Kehua; Li, Chang; Chang, Xiaotian
Abstract : Background . Rho guanine nucleotide exchange factor 10-like protein (ARHGEF10L) is a member of the guanine nucleotide exchange factor family, which regulates Rho GTPase activities, thus contributing to tumorigenesis. Our previous study demonstrated a strong association between the ARHGEF10L gene and the risk of cervical carcinoma. This study investigated the pathogenic role and mechanism of ARHGEF10L in cervical tumors. Methods . The HeLa cell line, which was derived from cervical carcinoma, was transfected with ARHGEF10L-overexpressing plasmids or anti-ARHGEF10L siRNA. Cell counting kit-8 assays, wound-healing assays, and cell apoptosis assays were performed to investigate the effects of ARHGEF10L on cell activities. A Rho pull-down assay and RNA-sequencing analysis were performed to investigate the pathogenic pathway of ARHGEF10L involvement in cervical tumors. Results . ARHGEF10L overexpression promoted cell proliferation and migration, reduced cell apoptosis, and induced epithelial-to-mesenchymal transition (EMT) via downregulation of E-cadherin and upregulation of N-cadherin and Slug in transfected HeLa cells. The overexpression of ARHGEF10L also upregulated GTP-RhoA, ROCK1, and phospho-ezrin/radixin/moesin (ERM) expression in HeLa cells. RNA-sequencing analysis detected altered transcription of 31 genes in HeLa cells with ARHGEF10L overexpression. Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene ontology (GO) pathway analyses identified significant differences in cyclin-dependent protein serine/threonine kinase activity, cell responses to vitamin A, and Toll-like receptor signaling pathways. Both real-time PCR and Western blotting verified the increased expression of heat shock 70 kDa protein 6 (HSPA6) in ARHGEF10L-overexpressing HeLa cells. Since we reported that ARHGEF10L played a role through RhoA-ROCK1-ERM signaling, an important pathway in tumorigenesis, and stimulated EMT and HSPA6 expression in liver tumors and gastric tumor cells, we suggest that ARHGEF10L is a novel oncogene in many tumors.